Annexation and Ethnicity in the American Midwest. (May 2014) - Wilson, Bev; Edwards, Mary M.
Prior research has established race as a factor in annexation decisions in the American South; however, there is very little research that examines the influence of ethnicity on annexation patterns. We consider a sample of incorporated places and their adjacent unincorporated blocks in 10 midwestern states to understand the relationship of ethnicity to annexation and possible differences in the drivers of annexation in metropolitan and nonmetropolitan contexts. The determinants of annexation in the Midwest differ in nonmetropolitan areas with existing population pressure and factors associated with capturing future growth as key drivers. Ethnicity appears to play a limited role in understanding annexation in the Midwest, but only within the nonmetropolitan context.